The developing of Marketing Mix Strategy & Using of QRIS As Supporting Purchasing Intention: A Systematic Literature Review - Adi Hermawansyah; Sudarmiatin Sudarmiatin; Agus Hermawan (International Journal of Economics and Management Sciences, 2025)
The Marketing Mix strategy is a combination of various marketing elements that include product, price, distribution place, and promotion. The Marketing Mix strategy, also known as the marketing mix is a concept in marketing that explains four main elements that must be managed in an integrated manner to achieve marketing objectives. In general practice, the using of QRIS is a payment standard using a QR code developed by Bank Indonesia and the Indonesian Payment System Association to simplify and accelerate digital transactions. Through VOSviewer analysis, the implementation of QRIS can have a positive impact on the operations and business performance of MSMEs, and the marketing mix strategy in the context of business digitalization becomes an important approach to maintaining MSME competitiveness. The results of the VOSviewer visual map analysis and the review of previous State of the Art research indicate that most existing studies still focus on aspects of QRIS adoption and transaction efficiency alone. These studies generally highlight how digital payment system is able to improve the speed, security, and convenience of transactions but have not yet widely linked them directly to marketing mix strategies and consumer purchasing decisions. This indicates a research gap in understanding the role of QRIS is not only as a transaction tool but also as part of the marketing strategy that influences consumer behaviour.